(untitled) (Journal of Educational Management, 2014)
This study is an action research conducted at the Aboom circuit of the Cape Coast Metropolis. It was aimed at exploring the idea of critical friendship between supervisor and supervisee to find out whether it can be useful in the Ghanaian context. The sample consisted of 31 participants, comprising one circuit supervisor, 26 teachers, and 4 headteachers. One out of the six circuits in the Cape Coast Metropolis was selected, and four schools from the circuit were randomly sampled for the study. The circuit supervisor and headteachers were interviewed, while questionnaires were administered to the teachers. Relationships and instructional practices in the school were also observed. The data were analysed using percentages. The main findings of the study were that critical friendship in instructional supervision increased the trust between the circuit supervisor and teachers, increased the supervisor’s support for teachers, and increased teachers’ commitment to their work. It was recommended that the Metropolitan Education Office educate circuit supervisors on the idea of critical friendship in supervision.